ColabSomGeo: Ferramenta de monitoramento de poluição sonora subsidiada por modelo de aprendizagem - Nery, Sannyer Cardoso Carvalho; Batista, Fani Tamires de Souza; Bezerra, Sergio Augusto Coelho (Anais Estendidos do Simpósio Brasileiro de Sistemas Multimídia e Web (WebMedia), 2025)
Sound pollution in urban centers is a public health issue, with excessive noise negatively impacting the physical and mental health of the population. Traditional monitoring methods are often costly, making widespread data collection difficult. This paper introduces ColabSomGeo, a low-cost, scalable web tool for visualizing and analyzing georeferenced sound pollution data. Data collection is performed collaboratively through a Telegram chatbot, where users submit audio recordings and their locations. A server application processes the data, classifies the noise type using a machine learning model, and stores the results. The tool aims to assist public managers in formulating policies, support scientific research, and raise public awareness about the impacts of noise on well-being. The code is available at:  https://github.com/colabsomgeo